SELECT DNA SEQUENCE ANALYSIS OF THE FANCONI ANEMIA COMPLEMENTATION GROUP A GENE, FANCA, IN DIVERSE GEOETHNIC CONTROL POPULATIONS - Hutchinson, Amy Ann (My University, 2005)
Fanconi anemia (FA) is a rare, autosomal recessive disorder characterized by bone marrow failure, a distinct dysmorpho logy and predisposition to certain cancers. Mutations within the FA complementation group A gene, FANCA, are responsible for up to 80% of Fanconi anemia cases. While greater than 200 FANCA mutations have been identified in patients, no comprehensive sequence analysis of non-disease causing alleles has been completed. In an effort to demonstrate how cancer predisposition in Fanconi anemia may be used as a model for the study of cancer susceptibility in healthy individuals, we have sequenced the FANCA gene in 402 control individuals from several geo-ethnic populations. Using sequencing data from two discrete regions of the FANCA gene, one area of high mutational rate and one of low mutational rate, we confirmed the hypothesis that genomic regions with a higher occurrence of disease-causing mutations would have a lower rate of genetic variation in normal populations.